FEATURES OF FORMING CLIENT ORIENTATION APPROACH, AT THE MARKET OF SOFTWAREOF UKRAINE - Тімофєєв, Володимир Олександрович; Кирій, Валентина Василівна; Бесараб, Денис Андрійович (Eastern-European Journal of Enterprise Technologies, 2013)
This article provides features and directions of development of companies - developers of software in Ukraine. The primary purpose of the article is generalization of the modern Ukrainian IТ companies’ experience and development of approaches and concepts of their further development in the conditions of high competition at the market with companies - giants of software industry. The necessity of the use of non-price factors of competitive activity was grounded. Using the elements of methodology of forming a marketing and competition strategy of an enterprise the work formulates characteristics of the conditions of transition to the client-oriented approach for IТ of companies as well as aims of such transition and its stages. The transition to client-oriented approach is an iterative process. Expediency of its use during a full company`s life cycle was grounded, its application will assist in adaptation of a company at the market. The suggested process of reorientation on a client can be used for elaboration of strategy of development by top-management of companies - developers of software.